DENSITY OF CONDENSATE OF WEAKLY INTERACTING BOSE GAS CONFINED BETWEEN TWO HARD WALLS IN IMPROVED HARTREE-FOCK APPROXIMATION - Nguyễn, Văn Thụ (Trường Đại học Đà Lạt, 2023)
By means of the Cornwall-Jackiw-Tomboulis effective potential, the condensate density of a weakly interacting Bose gas confined between two hard walls is investigated within an improved Hartree-Fock approximation (IHF). Our results show that the condensate density in an IHF approximation is always bigger than the one in a double-bubble approximation and that the condensate density strongly depends on the distance between two walls as well as the gas parameter.